Effect of gas–slag interaction on valorisation of refuse derived fuel treated with plasma gasification. (June 2015) - Yan, P.; Pandelaers, L.; Machiels, L.; Pontikes, Y.; Geysen, D.; Guo, M.; Blanpain, B.
<x content-type="archive" xml:space="preserve">Abstract</x> During gasification of refuse derived fuel (RDF) to produce syngas in a system in which a melt is also produced, the gasified organic fraction of the RDF is in contact with the molten inorganic fraction, i.e. a slag. Examples of such systems are plasma gasifiers, in which crude syngas is further cracked in a plasma converter. Depending on the degree of gas–slag interaction, their compositions may vary and influence the valorisation potential of both resources. To evaluate the influence of this interaction, a pseudo-kinetic model was developed based on local thermodynamic equilibrium between the gas phase and part of the slag phase. The interaction level was accounted for by varying the amount of the slag that equilibrates with the gas. The valorisation potential of the resulting gas and slag phases was evaluated in terms of the heat of combustion and the mineralogy after cooling, respectively. Engineering of the slag composition was made through lime-rich addition. The influence of waste composition on the gas/slag properties and the production of a metal phase was investigated.